Odpowiedzi

2009-11-17T21:29:10+01:00
A) 3x+πx=-π-3
3x+πx+π+3=0
x(3+π)+(π+3)=0
(x+1)(π+3)=0
Rozwiązaniem jest liczba -1.
2009-11-17T21:44:34+01:00
A) 3x+πx=-π-3
x(3+π)=-(3+π)
x=-1

b)(1-2√₃)(x-1)=2√₃-1
x-1-2√₃ x+2√₃=2√₃-1
x-2√₃ x=2√₃-1-2√₃+1
x-2√₃ x==0
x=0

c)3x=2+√₅+x√₅
3x-x√₅=2+√₅
x(3-√5)=2+√5
x=(2+√5)/(3-√5) /*(3+√5)/(3+√5)
x=(2+√5)(3+√5)/(3-√5) (3+√5)
x=(6+2√5+3√5+5) /3-5
x=(11+5√5)/-2
x=-5,5-2,5√5

d)x=1-√₂x
x+√2x=1
x(1+√2)=1
x=1/(1+√2) /*(1-√2)/(1-√2)
x=1(1-√2)/(1+√2) (1-√2)
x=(1-√2)/1-2
x=-1+√2

e)(x-2)³+10x²≥(x-2)(x+3)²
x³-6x²-12x-8+10x²≥(x-2)(x²+6x+9)
x³+4x²-12x-8≥x³+6x²+9x-2x²-12x-18
x³+4x²-12x-x³-6x²-9x+2x²+12x≥18+8
-9x≥26 /*(-1)
x≤-2 i 8/9

f)3√₂-x>1+2√₂
-x>1+2√₂-3√₂
-x>1-√2
x<-1+√2

g)3(x-4)²-2(2x+1)²≤14x-5x²
3(x²-8x+16)-2(4x²+4x+1)≤14x-5x²
3x²-24x+48-8x²-8x-2≤14x-5x²
3x²-24x-8x²-8x-14x+5x²≤2-48
-46x≤-46 /*(-1)
x≥1


h)x(x-2)(x+2)<5+x²(x+3)
x(x²-4)<5+x³+3x
x³-4x-x³-3x<5
-7x<5
x>-5/7